A new pale-spotted species of Hypostomus Lacépède (Siluriformes: Loricariidae) from the rio Tocantins and rio Xingu basins in central Brazil - Zawadzki,Cláudio H. (2008)
A new species of the genus Hypostomus Lacépède (Siluriformes, Loricariidae) from rio Tocantins and rio Xingu basins in central Brazil, is described. The new species is distinguished from its congeners by a unique combination of pale blotches over a darker background on head, body and fins, and conspicuous keels on head, predorsal region and lateral plates. Comments on the pale-spotted species of Hypostomus are provided.